Human Centered Design Second International Conference, HCD 2011, Held as Part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011. Proceedings - Kurosu, Masaaki; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This volume constitutes the refereed proceedings of the Second International Conference on Human Centered Design, HCD 2011, held as Part of HCI International 2011, in Orlando, FL, USA, in July 2011, jointly with 9 other thematically similar conferences. The 66 revised papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical parts on human centered design methods and tools, mobile and ubiquitous interaction, human centered design in health and rehabilitation, human centered design in work, business and education, and applications of human centered design.
Keywords: Computer science; Computer communication systems; Data mining; Multimedia information systems; User interfaces (Computer systems).; Artificial intelligence; Computer Science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Multimedia Information Systems; Data Mining and Knowledge Discovery; Computer Communication Networks; Electronic books